The pinch-off process of the leading vortex ring in a starting jet - Gao, Lei (2011)
The pinch-off of the leading vortex ring at a critical time scale, defined as the formation number (Gharib et al. 1998), has been identified as an important phenomenon for vortex ring formation in a starting jet. Previous researchers have also demonstrated the effect of non-impulsive velocity program on delaying the onset of pinch-off process and generating thicker vortex ring. Thus, experiments in present study focus on starting jets with different velocity programs and Reynolds numbers ($Re = 2600, 4100, 5600$) so as to determine the detailed characteristics of the pinch-off process. Digital Particle Image Velocimetry (DPIV) has been used to measure the velocity field, from which vorticity, circulation, impulse, kinetic energy and vortex ring trajectories can be derived. Based on the prediction on the dynamic fluxes fed into the leading vortex ring, an analytical model for the pinch-off process is subsequently developed.